IMPLEMENTASI SPELLING CHECKER DENGAN ALGORITMA LEVENSHTEIN DISTANCE PADA ENSIKLOPEDIA IT (Information Technology) BERBASIS WEBSITE - Jatminto, Joko; Kadek Dwi Nuryana, I (Inovate, 2016)
Knowledge of information technology is crucial in the era globalisai this time, many terms ofinformation technology that has not been understood and understood by the general public. To theknowledge of the information technology needs of the need for the central source of knowledge that canbe as references or resources.Language is a tool of human lingual communication both orally and in writing. Role of Indonesian andEnglish is good and right as the official language of national and international has a very importantmeaning as a description of information technology.Typing error checking and control language is good and true if done manually certainly will spend a lotof time, let alone an age of modern convenience such as this.Writing errors are mainly due to the proximity of the location of the keyboard, slip a finger, or becausethe two characters are located swapped. For the problems that came the idea to create a system of checking spelling or spelling checker in the encyclopedia of information technology based websitedeveloped using the programming language PHP and uses a database of vocabulary that refers to thecollection of licensing documents Copyright Â© 2003 IlmuKomputer.Com. Keywords: Information Technology, Writing Error, Based Website, Spelling checker,Encyclopedia